FOOD SECURITY IN THE FORMER YUGOSLAV REPUBLICS - Brankov, Tatjana; Lovre, Ivan (Economics of Agriculture, 2017)
The aim of this paper is to analyze food security in the former Yugoslav republics after they became independent nations. For that purpose we use new Food and Agriculture Organizations (FAO) suite of food security that provides possibility for a more nuanced assessment of food insecurity. The results do show some clear evidence of differences among countries. Compared with other ex-Yugoslav countries Slovenia is the most food secure country. It has the highest gross domestic product based on purchasing power parity (GDP PPP) as well as the highest value and growth rate of agricultural productivity. Bosnia and Herzegovina, Croatia, Montenegro, Serbia, and Macedonia are more vulnerable to food insecurity.